Student Errors Analysis on the Subject of Class VII Algebraic Form Based on Nolting's Theory - Azizah, Laily; Khoiri, Miftahul (Journal Focus Action of Research Mathematic (Factor M), 2022)
Tujuan penelitian ini adalah mendeskripsikan jenis dan faktor penyebab kesalahan yang dialami siswa kelas VII dalam bentuk aljabar berdasarkan Teori Nolting. Metode penelitian yang digunakan adalah deskriptif kualitatif. Subyek penelitian terdiri dari 10 siswa yang diambil secara acak, kemudian 2 siswa yang memenuhi 6 indikator tipe kesalahan Nolting diwawancarai. Berdasarkan hasil penelitian diketahui bahwa persentase jenis kesalahan yang dialami siswa adalah 50% mengalami misread direction errors, 20% mengalami careless errors, 10% mengalami concept errors, 25% mengalami application errors, 32,5% test taking errors, dan 7,5% mengalami study errors. Faktor penyebab kesalahan siswa adalah tidak memiliki referensi yang lengkap, kurang memperhatikan penjelasan guru, kurang mampu menangkap makna kata penting dalam soal, salah memahami soal, kurang memperdalam materi bentuk aljabar terutama dalam penerapan konsep operasi bentuk aljabar ke dalam bentuk soal cerita matematika, kurang melakukan latihan soal kontekstual, kurang teliti, terburu-buru, tidak mampu mengatur waktu pengerjaan. The purpose of this study is to describe the types and factors that cause errors experienced by class VII students in algebraic form based on Nolting's Theory. The research method used is descriptive qualitative. The research subjects consisted of 10 students who were taken randomly, then 2 students who met the 6 indicators of the Nolting error type were interviewed. Based on the results of the study, it is known that the percentage of types of errors experienced by students is 50% experiencing misread direction errors, 20% experiencing careless errors, 10% experiencing concept errors, 25% experiencing application errors, 32.5% test taking errors, and 7.5% experienced study errors. The factors that cause student errors are not having complete references, paying less attention to the teacher's explanations, not being able to capture the meaning of important words in questions, misunderstanding the questions, not deepening algebraic form material, especially in applying the concept of algebraic operations into the form of math story questions, not doing enough. contextual practice questions, less thorough, in a hurry, unable to manage the processing time.